Using KWL (Know, Want, and Learned) Strategy to Improve Students’ Reading Comprehension - Masruroh, Lailatul (International Journal of English Language and Pedagogy, 2024)
The Study is using KWL (know, want, and learned) straregy to improve students’ reading comprehension at SMA Ma’arif NU Assa'adah Bungah. The objective of this study is to describe the effectiveness of using KWL straregy to improve students’ reading comprehension. In this study, the design was classroom action Research (CAR). This study used some instruments such as observation sheets to observe the implementation of using KWL straregy, and field notes to write everything that happened during the act of conducting study. It consisted of two cycles; each cycles consisted of two meetings. This study used test, observation sheets, questionnaire and field notes to collect the data. In the first cycle, 95% of students gained the perfect score and passing the criteria of success. Meanwhile, the mean score of the first cycle is 88. But, according to teacher observered comment in the fieldnote. The students could get good score because the evaluation test was easy for them. The analysis result on the students’ ability in comprehending text in the second cycle informed that the mean score of their final assignment 100% or all of the students reached 90. So it passed of (MMC). It was also higher than previous score in the first cycle. Therefore, the students attained the criteria of the success after the implementation of the action on the second cycle which showed that KWL (know, want, and learned) straregy test is applicable in improving reading comprehension at SMA Ma’arif NU Assa'adah..